Impact of aeration rate on phosphorus conversion and bacterial community dynamics in phosphorus-enriched composting. (November 2022) - Ma, Tiantian; Zhan, Yabin; Chen, Wenjie; Xu, Shaoqi; Wang, Zhigang; Tao, Yueyue; Shi, Xiong; Sun, Baoru; Ding, Guochun; Li, Ji; Wei, Yuquan
Graphical abstract: Highlights: AR0.4 significantly increased the AP content and reached 36% P-solubilizing ratio. Aeration rate altered bacterial dynamics and key bacteria in P-enriched composting. AR0.4 had more orderly community organization for key bacteria to solubilize P. Key bacteria in indirect ways contributed more to P mobilization than directly ways. Abstract: This study was to investigate the effects of different aeration rates on phosphorus (P) conversion and bacterial community dynamics in P-enriched composting by 16S rRNA gene sequencing, sequential P fractionation, network analysis and structural equation model (SEM). Results indicated that Olsen P content increased by 138 %, 150 %, 121 % after composting with aeration rate (L kg −1 DM min −1 ) at 0.2 (AR0.2), 0.4 (AR0.4) and 0.6 (AR0.6). AR0.4 was more conducive to enhance P solubilization efficacy and available P accumulation. Redundancy analysis indicated Lactobacillus, Spartobacteria and Pseudomonas were key bacteria associated with HCl-Pi especially in AR0.2 and AR0.4. Network analysis showed that increased aeration rate enhanced the connection and function homoplasy among modules and AR0.4 had more orderly community organization for key bacteria to solubilize P in directly and indirectly biotic way. SEM suggested indirectly biotic P-solubilization had more contribution than directly biotic way mainly by phosphate-solubilizing bacteria.